2019
DOI: 10.1073/pnas.1820373116
|View full text |Cite
|
Sign up to set email alerts
|

Causal inference accounts for heading perception in the presence of object motion

Abstract: The brain infers our spatial orientation and properties of the world from ambiguous and noisy sensory cues. Judging self-motion (heading) in the presence of independently moving objects poses a challenging inference problem because the image motion of an object could be attributed to movement of the object, self-motion, or some combination of the two. We test whether perception of heading and object motion follows predictions of a normative causal inference framework. In a dual-report task, subjects indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 66 publications
4
72
0
Order By: Relevance
“…However, biases in heading perception are smaller than they would be if the object's motion were treated as a world-stationary landmark generating optic flow ( Raudies & Neumann, 2013 ). A causal inference model can account for biases in heading perception by predicting biases conditioned on whether an object is judged to be stationary ( Dokka et al, 2019 ). If an independently moving object is incorrectly judged to be stationary, its motion will be integrated with the optic flow produced by self-motion, generating biases in perceived heading.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, biases in heading perception are smaller than they would be if the object's motion were treated as a world-stationary landmark generating optic flow ( Raudies & Neumann, 2013 ). A causal inference model can account for biases in heading perception by predicting biases conditioned on whether an object is judged to be stationary ( Dokka et al, 2019 ). If an independently moving object is incorrectly judged to be stationary, its motion will be integrated with the optic flow produced by self-motion, generating biases in perceived heading.…”
Section: Discussionmentioning
confidence: 99%
“…This segmentation may occur in part automatically, as independently moving objects in the presence of optic flow appear to pop out to viewers (Rushton et al, 2007). Humans are more likely to detect independently moving objects that have larger speed mismatches with the inferred optic flow at the same location (Dokka, Park, Jansen, DeAngelis, & Angelaki, 2019;Royden & Connors, 2010;Royden, Parsons, & Travatello, 2016).…”
Section: Causal Inference and The Detection Of Moving Objectsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, if visual and vestibular heading cues are largely consistent, then it is likely that they have a common cause, and therefore information about heading provided by both cues should be integrated [8,3]. On the other hand, if a person is wearing a virtual reality headset but sitting still, then visual and vestibular cues would be inconsistent and the brain should segregate cue information [9]. The problem of inferring the cause of the cues is known as causal inference [10,11], and psychological evidence has shown that indeed the brain carries out such an operation [10,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Humans 6 integrate multisensory information in a near-optimal way according to Bayes' rule, and 7 it is desirable to understand how this is performed by underlying neural circuits. 8 9 The multisensory neurons in visual and vestibular brain areas, such as dorsal medial 10 superior temporal area (MSTd) and the ventral intraparietal (VIP) areas, can be 11 divided into two categories according to their tuning properties. One type of neurons is 12 called congruent neuron, as they prefer visual and vestibular cues of the same heading 13 directions ( Fig.…”
mentioning
confidence: 99%